Nuclear gamma-tubulin during acentriolar plant mitosis - Binarová, P; Cenklová, V; Hause, B; Kubátová, E; Lysák, M; Dolezel, J; Bögre, L; Dráber, P (The Plant cell, 2000)
Neither the molecular mechanism by which plant microtubules nucleate in the cytoplasm nor the organization of plant mitotic spindles, which lack centrosomes, is well understood. Here, using immunolocalization and cell fractionation techniques, we provide evidence that gamma-tubulin, a universal component of microtubule organizing centers, is present in both the cytoplasm and the nucleus of plant cells. The amount of gamma-tubulin in nuclei increased during the G(2) phase, when cells are synchronized or sorted for particular phases of the cell cycle. gamma-Tubulin appeared on prekinetochores before preprophase arrest caused by inhibition of the cyclin-dependent kinase and before prekinetochore labeling of the mitosis-specific phosphoepitope MPM2. The association of nuclear gamma-tubulin with chromatin displayed moderately strong affinity, as shown by its release after DNase treatment and by using extraction experiments. Subcellular compartmentalization of gamma-tubulin might be an important factor in the organization of plant-specific microtubule arrays and acentriolar mitotic spindles.
Keywords: Plants; Plants, Medicinal; Cell Nucleus; Fluorescent Antibody Technique; konfokální mikroskopie; fluorescenční protilátková technika; Mitosis; buněčné jádro; Fabaceae; rostliny; Microscopy, Confocal; Centrioles; Cell Cycle; centrioly; mitóza; buněčný cyklus; tubulin; léčivé rostliny; Tubulin